South African Food Security and Climate Change: Agriculture Futures - Dube, Sikhalazo; Scholes, Robert J.; Nelson, Gerald C.; Mason-D'Croz, Daniel; Palazzo, Amanda (ZBW - German National Library of Economics, 2013)
The projected changes in planted area, yield per area, net exports/imports and prices for five major agricultural crops in South Africa were simulated using the projections of four Global Circulation Models (GCMs) under three socio-economic scenarios. The GCM projections show consistent strong warming over the subcontinent, but disagree with respect to future precipitation, from slight wetting (particularly on the eastern side) to overall slight drying. The future crop yields were simulated using the DSSAT crop model suite. The planted area, commodity prices and net exports were simulated using the IMPACT global food trade model. The results indicate slightly rising to stable yields per unit area up to 2050, despite climate change, largely due to the inbuilt assumption of ongoing agronomic and genetic improvements. Vulnerability to food insecurity increases in the future under all but the most optimistic development scenarios, and is exacerbated by climate change, especially through global-scale, market- related mechanisms. Policies to increase local agricultural production in South Africa, decrease climate sensitivity and access to international markets are highlighted.